DEVELOPMENT AND VALIDATION OF THE TRAUMA‐INFORMED PRACTICE SCALES. Issue 6 (August 2016) - Goodman, Lisa A.; Sullivan, Cris M.; Serrata, Josie; Perilla, Julia; Wilson, Joshua M.; Fauci, Jennifer E.; DiGiovanni, Craig D.
Abstract : Spurred by research demonstrating the pervasiveness and impact of trauma, domestic violence programs are increasingly adopting a trauma‐informed approach. In the absence of measurement tools, however, they are unable to determine whether indeed clients experience their practices as trauma‐informed. The aim of this study was to create and validate a set of scales that measure the degree to which DV programs are using trauma informed practices (TIP) from survivors' perspectives. We generated measure items based on a literature review, interviews with experts, and focus groups with survivors and advocates; administered the draft measure in the context of a survey of 370 survivors from 15 DV programs; and evaluated its factor structure, reliability, and validity. Results supported the validity and reliability of the TIP Scales, which assess six domains: Environment of Agency and Mutual Respect, Access to Information on Trauma, Opportunities for Connection, Emphasis on Strengths, Cultural Responsiveness/Inclusivity, and Support for Parenting.